The Dual Impact of Economic Growth and Trade Openness in Explaining the Gender-Gap in Employment: Case of Arab Countries - altarawneh, yaseen; Al-Tal, Raad; Alomoush, Mariam (Journal of Ecohumanism, 2024)
This study aims at investigating the dual impact of trade openness and economic growth on gender-gap in employment for selected Arab countries in the last three decades. The panel data were extracted from the World Bank Indicators (WBI). To account for potential heterogeneity and non-stationarity in some series, the method of Weighted estimation for Dynamic Least Squares (DOLS) is used. The main findings substantiate the importance of both demand side factors such as economic growth and trade openness on gender-gap in employment as well as the supply side factors like education and fertility rate. The main variable of concern which is the trade openness has revealed as expected a positive and highly significant impact on gender-gap in employment. The GDP growth shows negative and significant impact on the gender-gap in employment, which was in favor of more male employment. Other factors such as education were no more drivers for more female employment but it might be driver for more female unemployment. It shows a negative impact for only young females but it was insignificant for other groups. Finally, fertility rates and urbanization have shown as expected a negative and significant impact on gender-gap in employment which still band more female employment with lack of convenient and affordable child care services.